I‐Xe ages of Campo del Cielo silicates as a record of the complex early history of the IAB parent body. (14th December 2013) - Pravdivtseva, O.; Meshik, A.; Hohenberg, C. M.; Kurat, G.
Abstract Using in situ laser analyses of a polished thin section from the IAB iron meteorite Campo del Cielo, we identified two silicate grains rich in radiogenic 129*Xe, Cr‐diopside, and oligoclase, excavated them from the metal, and irradiated them with thermal neutrons for I‐Xe dating. The release profiles of 129*Xe and 128*Xe are consistent with these silicates being diopside and oligoclase, with activation energies, estimated using Arrhenius plots, of ∼201 and ∼171 kcal mole−1, respectively. The 4556.4 ± 0.4 Ma absolute I‐Xe age of the more refractory diopside is younger than the 4558.0 ± 0.7 Ma I‐Xe age of the less refractory oligoclase. We suggest that separate impact events at different locations and depths on a porous initial chondritic IAB parent body led to the removal of the melt and recrystallization of diopside and oligoclase at the times reflected by their respective I‐Xe ages. The diopside and oligoclase grains were later brought into the studied inclusion by a larger scale catastrophic collision that caused breakup and reassembly of the debris, but did not reset the I‐Xe ages dating the first events. The metal melt most probably was <1250 °C when it surrounded studied silicate grains. This reassembly could not have occurred earlier than the I‐Xe closure in diopside at 4556.4 ± 0.4 Ma.